Comparative Analysis of Creative Assignments, Participatory Collaborative Learning, and Students’ Satisfaction in Digital & Non- Digital Learning Media - Budiningsih, Iffah; Oktapiani, Marliza; Rijanto, Widio; Masuwd, Mowafg Abrahem (FKIP Universitas Lampung, 2024)
Study Comparative of Creative Assignments, Participatory Collaborative Learning, and Learning Satisfaction in Digital & Non-Digital Learning Media.Objectives: This study aims to comparative of creative assignments, Participatory Collaborative Learning, and learning satisfaction in Digital & Non-Digital Learning. Methods: The study employed experimental and survey methods with a sample of seven State Aliyah Madrasah schools in East Jakarta. Each school consisted of two groups using digital learning media and two groups using non-digital media, randomly selected in the twelfth grade. Research instruments were previously tested for validity and reliability, and data analysis was conducted using the mean difference test (t-test). Findings: The findings are: (1) The creative assignment results in the group using digital media are higher than the non-digital media. (2) The participatory-collaborative learning activity is more active in the group using non-digital media than the digital media. (3) The student learning satisfaction in the group using non-digital media is higher than the digital media. Conclusion: This indicates that both digital and non-digital learning media have their respective advantages and disadvantages. Teachers are required to design creative tasks that follow learning objectives because different learning objectives will produce different learning outcomes even though the learning media is the same. Teachers must focus on determining the learning objectives of creative assignments and selecting the appropriate media. Keywords: creative assignment, participatory collaborative learning, learning satisfaction, digital and non-digital media.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024129